2013
DOI: 10.4172/2161-0509.s6-001
|View full text |Cite
|
Sign up to set email alerts
|

Statins Therapy: Effects on Plasma Fibrinogen Levels and Fibrinolysis

Abstract: Elevated plasma fibrinogen levels have been identified as an independent and strong risk factor for cardiovascular disease. At present, there are no selective oral agents that lower fibrinogen; however different drugs can influence its levels as ticlopidine (inhibitor of platelet aggregation) and fibrates (lipid lowering drugs). Statins lower cholesterol by inhibiting HMG-CoA (3-hydroxy-3-methylglutaryl-coenzyme A) reductase, which catalyzes the conversion of HMG-CoA to mevalonate, the rate limiting step in ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 103 publications
(117 reference statements)
0
3
0
Order By: Relevance
“…Moreover, Masuda et al reported on the downregulation of the CPB2 gene expression in HepG2 cells and decreases in both CPB2 mRNA and proCPU antigen levels, mediated by the PPARα signaling pathway upon treatment with the PPARα agonist WY14643 [ 17 ]. Since it has been described that statins increase PPARα expression (although they are not direct ligands for PPARα), the hypothesis that statin therapy could increase PPARα expression—which in turn could lead to reduced CPB2 gene expression and thus lower plasma proCPU levels—seems plausible but was not further explored in the current work [ 6 , 18 , 19 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Masuda et al reported on the downregulation of the CPB2 gene expression in HepG2 cells and decreases in both CPB2 mRNA and proCPU antigen levels, mediated by the PPARα signaling pathway upon treatment with the PPARα agonist WY14643 [ 17 ]. Since it has been described that statins increase PPARα expression (although they are not direct ligands for PPARα), the hypothesis that statin therapy could increase PPARα expression—which in turn could lead to reduced CPB2 gene expression and thus lower plasma proCPU levels—seems plausible but was not further explored in the current work [ 6 , 18 , 19 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Statins (inhibitors of 3-hydroxy-3-methyl-glutaryl coenzyme A reductase) exert cardiovascular protective effects that are independent of the lowering of LDL-cholesterol, including profibrinolytic effects such as the reduction of proCPU levels in hypercholesterolemic patients [ 5 , 6 , 7 , 8 ]. However, it is challenging to prove whether this is a lipid or a non-lipid-related pleiotropic effect, since lowering cholesterol is inherent to statin treatment in humans.…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of fibrinogen and alterations in fibrin clot properties could also be mediated by statins, which are used in the management of hyperlipidemia. Statins are associated with the modulation of PAI-1 and tPA activity, influence fibrinogen concentration, and have an impact on fibrinolysis [29][30][31]. Statins could increase the permeability of clots and thus enhance fibrinolysis [30].…”
Section: Discussionmentioning
confidence: 99%